Case Report: Urinary tract isolation of Cronobacter sakazakii in an oncohaematological patient in Southern Italy - Mecca, Antonella; Carrante, Debora; Mansueto, Giovanna Rosaria; Bianchino, Gabriella; Crispo, Fabiana; Campisi, Biagina (Frontiers in Oncology, 2026)
BackgroundCronobacter sakazakii is an emerging Gram-negative opportunistic pathogen, mostly associated with severe neonatal infections. In adults, infections are rare and usually occur in immuno-compromised or elderly patients. Urinary tract infections caused by C. sakazakii in oncological adults are extremely uncommon.CaseWe report a 66-year-old Caucasian male with acute myeloid leukaemia (AML) with a history of bladder carcinoma. The patient was admitted to the Haematology ward with fever (38.5°C), dysuria, pyuria, abdominal pain, and diarrhoea. He was already undergoing treatment at our Institute for AML and had completed the third cycle of liposomal daunorubicin/cytarabine (Vyxeos) 23 days prior to admission. Urine culture revealed C. sakazakii infection, confirmed on two different culture media. Blood and stool cultures were negative. The isolate was fully susceptible to all tested antibiotics. Empirical therapy with piperacillin/tazobactam was initiated, leading to rapid resolution of fever and urinary symptoms. Follow-up urine cultures after one week were negative, and the patient was discharged.ConclusionsThis case highlights a rare urinary tract infection caused by C. sakazakii in an immunocompromised adult. Conventional culture-based methods, with confirmation on two different media, enabled accurate identification of the pathogen. Prompt empirical antimicrobial therapy resulted in rapid clinical improvement and complete recovery. Reporting such cases contributes to awareness of this emerging pathogen in adult oncological patients and underscores the importance of culture-based diagnosis to guide effective management.